Perception of Fear of Crime Through Environmental Design: A Microscale Approach - Arévalo-García, Nataly Alejandra (Corporación Universitaria del Caribe, CECAR., 2021)
This study refines the evaluation of the perception of Fear of Crime (FoC) with its (in) tangible aspects using the Crime Prevention Through Environmental Design (CPTED) methodology. For this, a microscale approach based on the discipline of Environmental Psychology was built and applied in a university case study in Quito, Ecuador. The methodology is quantitative, descriptive in scope and cross-sectional. The non-probabilistic sample of 320 university students used a mobile participatory method and a victimization questionnaire. From there, foundations are laid for the CPTED theoretical-practical development.